2020
DOI: 10.1051/e3sconf/202014201006
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Content and Enhancing Plant resistance of Lowland Arabica Coffee

Abstract: The production of arabica coffee in Indonesia is still low because of leaf rust disease suppression caused by Hemileia vastatrix. Basically, it can produce well in the overlapping zone (1000-1500 masl). This potential can be used as basic for intensifying arabica coffee cultivation to the lowland. For anticipation steps to reduce the spread of leaf rust can be done by increasing the production of polyphenol as plant resistance. The addition of mineral element such as silica, boron, iodine, calcium, and potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Interesting results were obtained in the investigation of Wulanjari et al, who examined the impact of mineral elements (Si, B, Ca, K and I) as foliar treatments in arabica coffee leaves for improving plant disease resistance. 43 Their research demonstrated that aer application of iodine the average of polyphenol content in coffee leaves was over 2.5 times higher than the average of control plants. This is important, because an increased level of polyphenols in plants contributes to strengthening the cell walls that are crucial for protection against penetration of microorganisms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interesting results were obtained in the investigation of Wulanjari et al, who examined the impact of mineral elements (Si, B, Ca, K and I) as foliar treatments in arabica coffee leaves for improving plant disease resistance. 43 Their research demonstrated that aer application of iodine the average of polyphenol content in coffee leaves was over 2.5 times higher than the average of control plants. This is important, because an increased level of polyphenols in plants contributes to strengthening the cell walls that are crucial for protection against penetration of microorganisms.…”
Section: Discussionmentioning
confidence: 98%
“…This is important, because an increased level of polyphenols in plants contributes to strengthening the cell walls that are crucial for protection against penetration of microorganisms. 43 Skoczylas et al found that juices made from carrot fortified with an inorganic form of iodine was characterized by a significant increase in the concentration of ferulic, as well as caffeic and salicylic acids, in comparison to the juice obtained from non-enriched vegetables. 20 However, they showed that fertilization with iodine has a negative impact on the content of catechin in carrot juice.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main mechanisms of plant resistance to pathogen attack is through the production of secondary metabolites. Polyphenols are aromatic chemical compounds containing abundant phenolic groups that are divided into simple phenols, menolic acids, phenylpropenoids, coumarins, flavonoids, and tannins [42]. It has been reported that a higher proportion of polyphenols in coffee varieties may be associated with increased resistance to coffee leaf rust [42,43], although in susceptible varieties, there may be an increase in the content of total phenolic compounds during infection [38].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols are aromatic chemical compounds containing abundant phenolic groups that are divided into simple phenols, menolic acids, phenylpropenoids, coumarins, flavonoids, and tannins [42]. It has been reported that a higher proportion of polyphenols in coffee varieties may be associated with increased resistance to coffee leaf rust [42,43], although in susceptible varieties, there may be an increase in the content of total phenolic compounds during infection [38]. In this work, the application of PC chitosan increased the production of phenolic compounds after 48 h of pathogen inoculation, but this increase was not maintained after 72 h. Treatment with other elicitors, such as jasmonic acid, on coffee plants did not cause an increase in total phenolic compounds [43].…”
Section: Discussionmentioning
confidence: 99%
“…Rosyady et al (2020) mentions that mineral elements such as silica, iodine, and potassium can increase the plant resistance to attack by biotrophic fungi, such as H. vastatrix. Furthermore, Wulanjari et al (2020) also applied mineral element to coffee plants affected by leaf rust disease, and it showed decreasing in incidence by up to 78,13%. Based on the result of this study, these mineral elements have the potential to be formulated as supplements that can increase the natural resistance of plants in arabica coffee that have not been attacked by leaf rust disease.…”
Section: Introductionmentioning
confidence: 99%